An Analysis Of Compatibility On English Textbook Entitled Bright For The Seventh Grade Students Of Junior High School Based On Tomlinson's Theory - Novianti, Siska; , Djoko Srijono, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research paper aims at finding out whether the English textbook Entitled Bright for the seventh grade students of Junior High School is compatible or not with good criteria of English textbook proposed by Tomlinson and whether the textbook can increase students' ability. The writer applies descriptive study as the type of this research. The data are collected by using content analysis technique. The data in this study are the materials in the English textbook Bright. The writer uses descriptive analyses as the technique for analyzing data, the steps are: (1) defining criteria, (2) subjective analysis, (3) objective analysis, and (4) matching. The Tomlinson's criteria that suitable with Bright are (1) materials should be achieve impact, (2) materials should help learners to feel at ease, (3) materials should help learners to develop confidence, (4) materials should require and facilitate learner self-investment, (5) learners must be ready to acquire the points being taught, (6) the learners' attention should be drawn to linguistic features of the input, (7) materials should provide the learners with opportunities to use the target language to achieve communicative purposes, (8) materials should take into account that learners differ in learning style, (9) materials should take into account that learners differs in effective attitude, (10) materials should permit a silent period at the beginning of instruction, (11) materials should maximize learning potential by encouraging intellectual, aesthetic and emotional involvement which stimulates both right and left brain activities, and (12) materials should provide opportunities for outcome feedback. The result of this study shows that the English textbook Bright fulfills 75% of Tomlinson' theory, because fulfilled twelve criteria from sixteen criteria. This textbook can also increase students' ability because provided four abilities of English language ability those are writing, listening, reading, and speaking.